Comparison of clinical characteristics and mortality risk between patients with cholangiocarcinoma: A retrospective cohort study - Liu, Yaming; Wang, Yanhong; Yu, Yaqi; Luo, Haopeng; Zhen, Maochuan; Ren, Jianlin (Frontiers in Surgery, 2023)
Background Cholangiocarcinoma (CCA) is primary liver cancer originating from the biliary tract. The epidemiology of CCA is diverse across the globe. There are no reliably effective options for systemic therapy and CCA outcomes are poor. Herein, we examined the association between overall survival and clinical characteristics of CCA patients in our region. Methods We included 62 CCA cases diagnosed between 2015 and 2019. Demographics, clinical history, therapeutic procedures, and concomitant diseases were abstracted. Patient survival was obtained from a household registration system. Results The cohort was 69% male and 31% female, with 26 (42%) iCCA, 27 (44%) pCCA, and 9 (15%) dCCA. No age differences were observed between the three subtypes. Bile duct and metabolic disorders were the major concomitant diseases and showed varying associations with CCA subgroups. Serum triglycerides (TG) were higher in pCCA and dCCA than iCCA patients (p < 0.05), and TG and total cholesterol (TC) were highest among pCCA patients with cholelithiasis. Liver function appeared significant difference between iCCA, pCCA and dCCA subtypes (p < 0.01), and also in the subgroups without cholelithiasis (p < 0.01). The obstructive jaundice in pCCA patients was associated with survival time after surgery, and the presence of cholelithiasis was also another influential factor. Conclusion We found that pCCA was more frequently associated with metabolic disorders compared to iCCA and dCCA. Postoperative survival was also associated with the degree of jaundice in pCCA compared to iCCA or dCCA. And biliary drainage is an important predictor of outcome of pCCA.